Personal boundaries - Palmer, Vicki Tidwell (--For dummies., 2024)
"Learn how to create healthy personal and relationship boundaries. Boundaries are limits we establish for ourselves and implement through action or communication. Personal Boundaries For Dummies gives you all the basics on what boundaries look like (spoiler: they aren't "one-size-fits-all"), along with step-by-step instructions for figuring out what your boundaries are and communicating them with others. When you start to level-up your boundaries, you might experience pushback from the people in your life, but don't worry--this book also helps you navigate these challenges. Create clarity, mutual respect, and harmony in all your relationships--especially your relationship with yourself--with this clear and helpful Dummies guide. Explore the different types of boundaries and how they work in relationships; Identify your own limits and non-negotiables so you can set boundaries with others; Get advice on what to do when people don't respect your boundaries; Learn when to seek professional help. Setting boundaries is a form of self-care, and each of us must create boundaries for our own safety, health, and well-being.Get started with Personal Boundaries For Dummies!"--Publisher's description.